2008
DOI: 10.1118/1.2839329
|View full text |Cite
|
Sign up to set email alerts
|

The effective point of measurement of ionization chambers and the build‐up anomaly in MV x‐ray beams

Abstract: A precision experimental investigation of the effective point of measurement (EPOM) of ion chambers in megavoltage beams has been carried out. A one-dimensional scanning phantom system was developed with an overall accuracy in the positioning of a chamber of better than 0.15 mm. Depth-dose data were acquired for a 25 MV beam from an Elekta Precise linac (field sizes of 10 x 10 cm and 25 x 25 cm) for measurement depths in the range 0.6-6 cm. The results confirmed the Monte Carlo calculations of an earlier theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 12 publications
7
70
0
Order By: Relevance
“…The NACP chamber has a “coin‐shaped” sensitive volume with a diameter of 10 mm, a height of 2 mm and a guard ring of 3 mm in width (24) . In the literature a guard ring of at least 5 mm is recommended for measuring skin doses, (16) but both Carl and Vestergaard (1) and McEwen et al (21) have investigated its use and found it to be suitable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NACP chamber has a “coin‐shaped” sensitive volume with a diameter of 10 mm, a height of 2 mm and a guard ring of 3 mm in width (24) . In the literature a guard ring of at least 5 mm is recommended for measuring skin doses, (16) but both Carl and Vestergaard (1) and McEwen et al (21) have investigated its use and found it to be suitable.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the product Pfl,Pitalicwall,Pitaliccell changes by less than 1% from the surface to normaldmax 20 , 21 and that false(LΔ¯/ρfalse)italicairitalicmed changes by less than 4% for beams up to 18 MV. The maximum deviation occurs at the phantom surface and will be less than 5%, reducing to 0% at normaldmax.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During depth-dose measurements, this correction can be equivalently dealt with by reporting absorbed dose at an effective point of measurement, which for energyspecific reference conditions depends only on chamber materials and geometry. 17,18 For nonreference conditions, where the dose gradient is not known a priori, this physical effect is not predictable and therefore reporting dose at a point of measurement is no longer appropriate for general measurement conditions. Previous studies 19,20 have demonstrated the invalidity of the application of standard absorbed dose protocols ͓e.g., AAPM TG-51 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There is an excellent book summarising the ISO GUM published by the National Measurement Institute of Australia [6]. Finally, there are a number of medical physics papers that have used the ISO GUM methodology to determine an uncertainty budget [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%